Radiocarbon chronology of the early human occupation of Argentina - Prates, Luciano Raúl (2013)
This paper reports the compilation and initial analysis of a database of 14C dates from archaeological sites in Argentina for the period 13,000 and 7000 14C BP. The spatial and temporal distribution of human occupation evidence during this period is surveyed, with discussion of potential sampling biases affecting the recognition of such sites in each region of Argentina. The archaeological signal of human occupation at the beginning of this period (13,000-11,000 14C BP) is suggestive but sparse, and weak. However, from about 11,000 14C BP there is a consistent archaeological signal. Most of the earliest occupation evidence comes from the eastern Pampas and from southern Patagonia. In the Chaco and Northeast regions, similarly early archaeological sites have not yet been detected. This contrast may reflect the actual distribution of early human occupation, but it may also reflect biased research effort and/or systemic factors affecting the visibility and level of preservation of the early archaeological record. In other regions such as the eastern slope of the Andes in Patagonia, the peri-Andean Central West, and the Northwest, where there has been intensive archaeological research for an extended period and there are fewer systematic factors which are likely to bias archaeological visibility, the absence of archaeological evidence of early occupation may indicate delayed colonization of these more marginal environments. The conclusion discusses the implications of 14C dates associated with Fishtail Projectile Points for the western hemisphere pre-Clovis debate, and the implications of terminal Pleistocene/early Holocene dated remains of extinct mammals for the megafaunal overkill hypothesis.